Research on the Impact of Regional Business Environment on Corporate Equity Structure - Lu, Tian; Wu, Yanbo; Zhang, Junjia (Edelweiss Applied Science and Technology, 2025)
Based on resource dependence theory, this study takes Chinese A-share listed companies from 2009 to 2023 as samples, adopting panel fixed-effects models and mediation effect tests to explore how the regional business environment impacts corporate equity structure. Key findings: (1) Optimizing the business environment significantly reduces the proportion of state-owned enterprises. For every unit increase in the regional business environment index (BHAR), the probability of state-owned enterprises decreases by 3.16%, verifying the theoretical path of "improving the institutional environment weakening resource dependence optimizing equity structure"; (2) regional heterogeneity exists: the effect is significant in eastern China but insignificant in central and western regions, reflecting the synergy of institutional quality and market maturity; (3) the business environment promotes equity diversification by reducing corporate financialization. Innovatively integrating the business environment into corporate governance analysis, the study reveals external institutional impacts on ownership arrangements, providing theoretical and empirical support for targeted policy optimization and coordinated reform, with implications for high-quality economic development.